Digitalisasi Pemasaran Umkm Kerupuk Melalui Pemanfaatan Media Sosial dan E-Commerce - Muhammad Aril Frianto; Rama Soleman; Siti Marwani; Rahma Ade Mulyanti; Nasywa Faadiyah; Neni Sarbinny; Azzahra Yang Ditta; Dian Rinanda Novitasar; Uswatun Hasanah; Marifatul Hikmah (LP3M IAIFA Kediri, 2025)
The development of digital technology is driving changes in marketing strategies in the Micro, Small, and Medium Enterprises (MSMEs) sector. However, many MSME actors have not yet optimally utilized digital media, especially in product marketing. KKN aims to describe the process and impact of MSME marketing digitalization of crackers through the use of social media and e-commerce platforms at the Lima Saudara cracker production house. The method used is a participatory approach with stages of observation, visual identity design, digital marketing implementation, and evaluation. The results of the activity show an increase in the understanding of MSME actors regarding digital marketing, the formation of brand identities in the form of logo and banners, as well as the opening of wider market access through social media and e-commerce. Marketing digitalization has proven to be an effective strategy in sustainably enhancing the competitiveness of MSME crackers.